Opening of the outer membrane protein channel in tripartite efflux pumps is induced by interaction with the membrane fusion partner. - Janganan, T; Zhang, L; Bavro, V; Matak-Vinkovic, D; Barrera, N; Burton, M; Steel, P; Robinson, C; Borges-Walmsley, M; Walmsley, A (2011)
The multiple transferable resistance (MTR) pump, from Neisseria gonorrhoeae, is typical of the specialized machinery used to translocate drugs across the inner and outer membranes of Gram-negative bacteria. It consists of a tripartite complex composed of an inner-membrane transporter, MtrD, a periplasmic membrane fusion protein, MtrC, and an outer-membrane channel, MtrE. We have expressed the components of the pump in Escherichia coli and used the antibiotic vancomycin, which is too large to cross the outer-membrane by passive diffusion, to test for opening of the MtrE channel. Cells expressing MtrCDE are not susceptible to vancomycin, indicating that the channel is closed; but become susceptible to vancomycin in the presence of transported substrates, consistent with drug-induced opening of the MtrE channel. A mutational analysis identified residues Asn-198, Glu-434, and Gln-441, lining an intraprotomer groove on the surface of MtrE, to be important for pump function; mutation of these residues yielded cells that were sensitive to vancomycin. Pull-down assays and micro-calorimetry measurements indicated that this functional impairment is not due to the inability of MtrC to interact with the MtrE mutants; nor was it due to the MtrE mutants adopting an open conformation, because cells expressing these MtrE mutants alone are relatively insensitive to vancomycin. However, cells expressing the MtrE mutants with MtrC are sensitive to vancomycin, indicating that residues lining the intra-protomer groove control opening of the MtrE channel in response to binding of MtrC.